Strategies aimed at controlling misuse and abuse of opioid prescription medications in a state Medicaid program: a policymaker's perspective. (January 2015) - Keast, Shellie L.; Nesser, Nancy; Farmer, Kevin
Abstract Society in America, like many others, continues to wrestle with the problem of misuse and abuse of prescription opioids. The implications of this struggle are widespread and involve many individuals and institutions including healthcare policymakers. State Medicaid pharmacy programs, in particular, undergo significant scrutiny of their programs to curtail this problem. While recent efforts have been made by government agencies to both quantify and offer methods for curbing this issue, it still falls to each state's policymakers to protect its resources and the population it serves from the consequences of misuse and abuse. This paper details the history of one state Medicaid's management of this issue at the pharmacy benefit level. Examples of various methods employed and the results are outlined and commentary is provided for each method. Regardless of the methods used to address this issue, the problem must still be a priority at all levels, not just for payers.